State of practice of user-developer communication in large-scale it projects - Abelein, Ulrike; Paech, Barbara (Requirements Engineering: Foundation for Software Quality, 2014)
[Context and motivation] User participation in software development is considered to be essential for successful software systems. Especially missing direct communication between users and developers can cause various issues in large-scale IT projects. [Question/Problem] We want to understand current practices of user-developer communication in large-scale IT projects, the factors for, and consequences of communication gaps, and what experts suggest to prevent them. [Principal ideas/results]: We conducted a series of semi-structured interviews with twelve experts. The experts work on the coordination of Business and IT and describe their experiences gained in 69 large-scale IT projects. The analysis of our interviews showed that direct user- developer communication is limited and that no commonly used method for the user-developer communication in the design and implementation activity exists. [Contribution]: The interviews helped us to understand current practices and issues resulting from missing communication. Furthermore, we can confirm the need for a method enhancing user-developer-communication in large-scale IT projects.
Gesehen am 30.07.2017